Slope failure risk assessment considering climate change using analytical hierarchy process: a case study in Singapore - Gee, Ervin Soo Jun (Nanyang Technological University, 2023)
In recent years, the topic on climate change has been an increasing concern of the global population. Climate change is one of the most significant challenges that our planet face today and it results in detrimental impacts. Impacts such as increase in duration and intensity of rainfall can bring about disastrous consequences like flooding and erosion. Singapore has not been spared from these negative impacts which are due to climate change. Slope failure because of increase in rainfall amount due to climate change has become a serious concern in Singapore. To accurately evaluate the slope failure risk in Singapore, this report utilises the Analytical Hierarchal Process (AHP) approach which is based on the likelihood and consequence index system with each system consisting of 3 influential factors each. Maximum daily rainfall, slope angle and soil permeability are factors under the likelihood index while population density, land use type and distance to nearest civil defence station are part of the consequence index. Through the AHP process, the weightage for each factor is generated and the final slope failure risk level is obtained by the summation of the product of the weightage and normalised factor value of each factor. Additionally, a sensitivity analysis is also conducted to determine which of the influential factors have a greater influence in slope failure risk so that effective and appropriate measures can be implemented to mitigate the harmful effects of these factors. To verify the effectiveness and applicability of the approach, a case study which comprise of 2 slopes in Singapore are conducted. The slopes comprise of the NTU SCSE slope, and the slope located at Serangoon North Ave 5. From the results obtained, it is determined that the slope at NTU SCSE has a higher slope failure risk value, and the sensitivity analysis is consistent with the AHP factor weightage. Overall, it can be determined that the AHP method is effective not only in identifying the factors that cause slope failure risk due to climate change, but also effective in evaluating the slope failure risk of a specific slope.